Assessment of formation of static biofilm from environmental isolates of pseudomonas aeruginosa and study of their antibiotic resistance pattern - Chowdhury, Sara Sadia (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.